AMPA-receptor specific biogenesis complexes control synaptic transmission and intellectual ability - Brechet, Aline; Buchert, Rebecca; Schwenk, Jochen; Boudkkazi, Sami; Zolles, Gerd; Siquier-Pernet, Karine; Schaber, Irene; Bildl, Wolfgang; Saadi, Abdelkrim; Bole-Feysot, Christine; Nitschke, Patrick; Reis, André; et al. (Nature Communications, 2017)
AMPA-type glutamate receptors (AMPARs), key elements in excitatory neurotransmission in the brain, are macromolecular complexes whose properties and cellular functions are determined by the co-assembled constituents of their proteome. Here we identify AMPAR complexes that transiently form in the endoplasmic reticulum (ER) and lack the core-subunits typical for AMPARs in the plasma membrane. Central components of these ER AMPARs are the proteome constituents FRRS1l (C9orf4) and CPT1c that specifically and cooperatively bind to the pore-forming GluA1-4 proteins of AMPARs. Bi-allelic mutations in the human FRRS1L gene are shown to cause severe intellectual disability with cognitive impairment, speech delay and epileptic activity. Virus-directed deletion or overexpression of FRRS1l strongly impact synaptic transmission in adult rat brain by decreasing or increasing the number of AMPARs in synapses and extra-synaptic sites. Our results provide insight into the early biogenesis of AMPARs and demonstrate its pronounced impact on synaptic transmission and brain function.
EVALuna2:9374

A Peroxisomal Disorder of Severe Intellectual Disability, Epilepsy, and Cataracts Due to Fatty Acyl-CoA Reductase 1 Deficiency - Buchert, Rebecca; Tawamie, Hasan; Smith, Christopher; Uebe, Steffen; Innes, A. Micheil; Al Hallak, Bassam; Ekici, Arif Bülent; Sticht, Heinrich; Schwarze, Bernd; Lamont, Ryan E.; Parboosingh, Jillian S.; Bernier, Francois P.; et al. (American Journal of Human Genetics, 2014)
Rhizomelic chondrodysplasia punctata (RCDP) is a group of disorders with overlapping clinical features including rhizomelia, chondrodysplasia punctata, coronal clefts, cervical dysplasia, congenital cataracts, profound postnatal growth retardation, severe intellectual disability, and seizures. Mutations in PEX7, GNPAT, and AGPS, all involved in the plasmalogen-biosynthesis pathway, have been described in individuals with RCDP. Here, we report the identification of mutations in another gene in plasmalogen biosynthesis, fatty acyl-CoA reductase 1 (FAR1), in two families affected by severe intellectual disability, early-onset epilepsy, microcephaly, congenital cataracts, growth retardation, and spasticity. Exome analyses revealed a homozygous in-frame indel mutation (c.495_507delinsT [p.Glu165_Pro169delinsAsp]) in two siblings from a consanguineous family and compound-heterozygous mutations (c.[787C>T];[1094A>G], p.[Arg263(*)];[Asp365Gly]) in a third unrelated individual. FAR1 reduces fatty acids to their respective fatty alcohols for the plasmalogen-biosynthesis pathway. To assess the pathogenicity of the identified mutations, we transfected human embryonic kidney 293 cells with plasmids encoding FAR1 with either wild-type or mutated constructs and extracted the lipids from the cells. We screened the lipids with gas chromatography and mass spectrometry and found that all three mutations abolished the reductase activity of FAR1, given that no fatty alcohols could be detected. We also observed reduced plasmalogens in red blood cells in one individual to a range similar to that seen in individuals with RCDP, further supporting abolished FAR1 activity. We thus expand the spectrum of clinical features associated with defects in plasmalogen biosynthesis to include FAR1 deficiency as a cause of syndromic severe intellectual disability with cataracts, epilepsy, and growth retardation but without rhizomelia.
EVALuna2:9238

Diagnostic Yield and Novel Candidate Genes by Exome Sequencing in 152 Consanguineous Families With Neurodevelopmental Disorders - Reuter, Miriam; Tawamie, Hasan; Buchert, Rebecca; Gebril, Ola Hosny; Froukh, Tawfiq; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Zweier, Christiane; Hoyer, Juliane; Eberlein, Karolin; et al. (JAMA Psychiatry, 2017)
Autosomal recessive inherited neurodevelopmental disorders are highly heterogeneous, and many, possibly most, of the disease genes are still unknown.To promote the identification of disease genes through confirmation of previously described genes and presentation of novel candidates and provide an overview of the diagnostic yield of exome sequencing in consanguineous families.Autozygosity mapping in families and exome sequencing of index patients were performed in 152 consanguineous families (the parents descended from a same ancestor) with at least 1 offspring with intellectual disability (ID). The study was conducted from July 1, 2008, to June 30, 2015, and data analysis was conducted from July 1, 2015, to August 31, 2016.Of the 152 consanguineous families enrolled, 1 child (in 45 families [29.6%]) or multiple children (107 families [70.4%]) had ID; additional features were present in 140 of the families (92.1%). The mean (SD) age of the children was 10.3 (9.0) years, and 171 of 297 (57.6%) were male. In 109 families (71.7%), potentially protein-disrupting and clinically relevant variants were identified. Of these, a clear clinical genetic diagnosis was made in 56 families (36.8%) owing to 57 (likely) pathogenic variants in 50 genes already established in neurodevelopmental disorders (46 autosomal recessive, 2 X-linked, and 2 de novo) or in 7 previously proposed recessive candidates. In 5 of these families, potentially treatable disorders were diagnosed (mutations in PAH, CBS, MTHFR, CYP27A1, and HIBCH), and in 1 family, 2 disease-causing homozygous variants in different genes were identified. In another 48 families (31.6%), 52 convincing recessive variants in candidate genes that were not previously reported in regard to neurodevelopmental disorders were identified. Of these, 14 were homozygous and truncating in GRM7, STX1A, CCAR2, EEF1D, GALNT2, SLC44A1, LRRIQ3, AMZ2, CLMN, SEC23IP, INIP, NARG2, FAM234B, and TRAP1. The diagnostic yield was higher in individuals with severe ID (35 of 77 [45.5%]), in multiplex families (42 of 107 [39.3%]), in patients with additional features (30 of 70 [42.9%]), and in those with remotely related parents (15 of 34 [44.1%]).Because of the high diagnostic yield of 36.8% and the possibility of identifying treatable diseases or the coexistence of several disease-causing variants, using exome sequencing as a first-line diagnostic approach in consanguineous families with neurodevelopmental disorders is recommended. Furthermore, the literature is enriched with 52 convincing candidate genes that are awaiting confirmation in independent families.
EVALuna2:9388

Inhibition of RAS activation due to a homozygous ezrin variant in patients with profound intellectual disability - Riecken, Lars Bjoern; Tawamie, Hasan; Dornblut, Carsten; Buchert, Rebecca; Ismayel, Amina; Schulz, Alexander; Schumacher, Johannes; Sticht, Heinrich; Pohl, Katja J.; Cui, Yan; Reis, André; Morrison, Helen; et al. (Human Mutation, 2015)
Gain-of-function alterations in several components and modulators of the Ras-MAPK pathway lead to dysregulation of the pathway and cause a broad spectrum of autosomal dominant developmental disorders, collectively known as RASopathies. These findings demonstrate the importance of tight multilevel Ras regulation to safeguard signaling output and prevent aberrant activity. We have recently identified ezrin as a novel regulatory element required for Ras activation. Homozygosity mapping and exome sequencing have now revealed the first presumably disease-causing variant in the coding gene EZR in two siblings with a profound intellectual disability. Localization and membrane targeting of the altered ezrin protein appeared normal but molecular modeling suggested protein interaction surfaces to be disturbed. Functional analysis revealed that the altered ezrin protein is no longer able to bind Ras and facilitate its activation. Furthermore, expression of the altered ezrin protein in different cell lines resulted in abnormal cellular processes, including reduced proliferation and neuritogenesis, thus revealing a possible mechanism for its phenotype in humans. To our knowledge, this is the first report of an autosomal recessively inherited loss-of-function mutation causing reduced Ras activity and thus extends and complements the pathogenicity spectrum of known Ras-MAPK pathway disturbances.
EVALuna2:9253

Mutations in DCPS and EDC3 in autosomal recessive intellectual disability indicate a crucial role for mRNA decapping in neurodevelopment - Ahmed, Iltaf; Buchert, Rebecca; Zhou, Mi; Jiao, Xinfu; Mittal, Kirti; Sheikh, Taimoor I.; Scheller, Ute; Vasli, Nasim; Rafiq, Muhammad Arshad; Brohi, M. Qasim; Mikhailov, Anna; Ayaz, Muhammad; et al. (Human Molecular Genetics, 2015)
There are two known mRNA degradation pathways, 3' to 5' and 5' to 3'. We identified likely pathogenic variants in two genes involved in these two pathways in individuals with intellectual disability. In a large family with multiple branches, we identified biallelic variants in DCPS in three affected individuals; a splice site variant (c.636+1G>A) that results in an in-frame insertion of 45 nucleotides and a missense variant (c.947C>T; p.Thr316Met). DCPS decaps the cap structure generated by 3' to 5' exonucleolytic degradation of mRNA. In vitro decapping assays showed an ablation of decapping function for both variants in DCPS. In another family, we identified a homozygous mutation (c.161T>C; p.Phe54Ser) in EDC3 in two affected children. EDC3 stimulates DCP2, which decaps mRNAs at the beginning of the 5' to 3' degradation pathway. In vitro decapping assays showed that altered EDC3 is unable to enhance DCP2 decapping at low concentrations and even inhibits DCP2 decapping at high concentration. We show that individuals with biallelic mutations in these genes of seemingly central functions are viable and that these possibly lead to impairment of neurological functions linking mRNA decapping to normal cognition. Our results further affirm an emerging theme linking aberrant mRNA metabolism to neurological defects.
EVALuna2:9274

Null mutation in PGAP1 impairing Gpi-anchor maturation in patients with intellectual disability and encephalopathy - Murakami, Yoshiko; Tawamie, Hasan; Maeda, Yusuke; Büttner, Christian; Buchert, Rebecca; Radwan, Farah; Sticht, Heinrich; Aigner, Michael; Reis, André; Kinoshita, Taroh; Abou Jamra, Rami; et al. (PLoS Genetics, 2014)
Many eukaryotic cell-surface proteins are anchored to the membrane via glycosylphosphatidylinositol (GPI). There are at least 26 genes involved in biosynthesis and remodeling of GPI anchors. Hypomorphic coding mutations in seven of these genes have been reported to cause decreased expression of GPI anchored proteins (GPI-APs) on the cell surface and to cause autosomal-recessive forms of intellectual disability (ARID). We performed homozygosity mapping and exome sequencing in a family with encephalopathy and non-specific ARID and identified a homozygous 3 bp deletion (p.Leu197del) in the GPI remodeling gene PGAP1. PGAP1 was not described in association with a human phenotype before. PGAP1 is a deacylase that removes an acyl-chain from the inositol of GPI anchors in the endoplasmic reticulum immediately after attachment of GPI to proteins. In silico prediction and molecular modeling strongly suggested a pathogenic effect of the identified deletion. The expression levels of GPI-APs on B lymphoblastoid cells derived from an affected person were normal. However, when those cells were incubated with phosphatidylinositol-specific phospholipase C (PI-PLC), GPI-APs were cleaved and released from B lymphoblastoid cells from healthy individuals whereas GPI-APs on the cells from the affected person were totally resistant. Transfection with wild type PGAP1 cDNA restored the PI-PLC sensitivity. These results indicate that GPI-APs were expressed with abnormal GPI structure due to a null mutation in the remodeling gene PGAP1. Our results add PGAP1 to the growing list of GPI abnormalities and indicate that not only the cell surface expression levels of GPI-APs but also the fine structure of GPI-anchors is important for the normal neurological developmen
EVALuna2:9210

SPATA5 mutations cause a distinct autosomal recessive phenotype of intellectual disability, hypotonia and hearing loss - Buchert, Rebecca; Nesbitt, Addie I.; Tawamie, Hasan; Krantz, Ian D.; Medne, Livija; Helbig, Ingo; Matalon, Dena R.; Reis, André; Santani, Avni; Sticht, Heinrich; Abou Jamra, Rami (Orphanet Journal of Rare Diseases, 2016)
We examined an extended, consanguineous family with seven individuals with severe intellectual disability and microcephaly. Further symptoms were hearing loss, vision impairment, gastrointestinal disturbances, and slow and asymmetric waves in the EEG. Linkage analysis followed by exome sequencing revealed a homozygous variant in SPATA5 (c.1822_1824del; p.Asp608del), which segregates with the phenotype in the family. Molecular modelling suggested a deleterious effect of the identified alterations on the protein function. In an unrelated family, we identified compound heterozygous variants in SPATA5 (c.[2081G > A];[989_991delCAA]; p.[Gly694Glu];[.Thr330del]) in a further individual with global developmental delay, infantile spasms, profound dystonia, and sensorineural hearing loss. Molecular modelling suggested an impairment of protein function in the presence of both variants.SPATA5 is a member of the ATPase associated with diverse activities (AAA) protein family and was very recently reported in one publication to be mutated in individuals with intellectual disability, epilepsy and hearing loss. Our results describe new, probably pathogenic variants in SPATA5 that were identified in individuals with a comparable phenotype. We thus independently confirm that bi-allelic pathogenic variants in SPATA5 cause a syndromic form of intellectual disability, and we delineate its clinical presentation.
EVALuna2:9313